Precursor and product processing in the bag cell neurons of Aplysia californica (The Rockefeller University Press, 1976)
Posttranslational processing in the biosynthesis of the egg-laying hormone (ELH) by the bag cell neurons of Aplysia californica was studied. The precursor (pro-ELH) to ELH was found to be resistant to solubilization in denaturant-free media throughout its lifetime. Its principle products show a similar insolubility for 3 h, but two of these, ca. 6,000 daltons, subsequently become readily recoverable in the low-speed supernatant of a homogenate of the cells. The remaining product shows no change in solubility characteristics. From studies employing ultracentrifugation and examination of axoplasmic transport, the solubility shift for the lower molecular weight products is interpreted to represent the liberation of secretory vesicles into the cytoplasm from larger membranous associations. This event is accompanied by, but does appear to be dependent upon, a 15% reduction in the molecular weight of one of the products. These findings are considered in the light of the extensively studied posttranslational processing regimen for the production of insulin in the pancreatic beta cell.